A novel, nontoxic iron chelator, super-polyphenol, effectively induces apoptosis in human cancer cell lines - Ohara, Toshiaki (Oncotarget, 2018)
Iron chelation therapy is the main treatment for iron overload disease. Iron chelators were recently reported to be useful for cancer therapy; however, they cause side effects that make them difficult to use in some cancer patients. Thus, a novel oral iron chelator, super-polyphenol (SP), was developed for cancer therapy to decrease the side effects. SP is either water soluble or insoluble, and has different isoforms according to the number of side chains. Of these isoforms, water-soluble SP6 and SP10 appear to be the best candidates, as they have the strongest chelating abilities. In this study, we focused on the usefulness and safety of SP6 and SP10 as anti-cancer drugs, and examined their anti-cancer effects and toxicity. The results showed that SP6 and SP10 inhibited cancer cell proliferation by inducing apoptosis in HCT116, HSC-2, A549, and MCF-7 cancer cells. SP10 also inhibited tumor growth in an HCT116 xenograft model. SP6 and SP10 had no acute toxicities. An intravenous injection test revealed that SP6 and SP10 had better safety profiles than the iron chelator deferoxamine. In conclusion, SP is a novel oral iron chelator with anti-cancer effects and few adverse side effects. This is the first report of SP in the literature.